2021
DOI: 10.25130/tjas.21.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Protein Ratio In Fattening Diet On Performance Production And Some Biochemical Characteristics Of Blood In Awassi Lambs

Abstract: This study was conducted in the animal field of the College of Agriculture University of Tikrit for a period of 70days precession this period 14 day as adaptation starting from 8/10/2020 to 16/12/2020. Sixteen Awassi lambs were used, aged 5-6 months, with an average weight of 26.2 ± 0.3 kg. The experimental treatments were, first, the control 98% barley (farmer diet), the second 88% barley + 5% soybean meal+ 5% vegetable fat and the third 83% barley + 10% Soybean meal+ 5% fat and the fourth 78% barley + 15% so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The results of the statistical analysis also indicated that there was a significant superiority (P≤0.05) for the high-protein treatments over the low-protein treatments in each of the final body weight (33.35) kg and (31.23) kg and empty body weight (29.56) kg and (27.41) kg, respectively. These results agreed with the results of the study of the researcher [24], where they found an increase in the final weight whenever the percentage of protein in the diet increased when using different levels of protein, where the lambs were fed levels (110,140,170 and 200) g/kg, This study also agreed with the researchers' study [25] where the high protein treatments were superior in final body weight to the control treatment, These results also agreed with what was found by [26], where they indicated that the final weight and empty body weight increased when lambs were fed high-protein diets, while they did not agree with what was found by [27], where they did not show any differences. Significant when using diets with a protein level (14,16,18 and 20%), also did not agree with what [28] indicated, because there were no significant differences when feeding the study lambs on diets with protein content (11,16%).…”
Section: Final and Empty Body Weightsupporting
confidence: 90%
“…The results of the statistical analysis also indicated that there was a significant superiority (P≤0.05) for the high-protein treatments over the low-protein treatments in each of the final body weight (33.35) kg and (31.23) kg and empty body weight (29.56) kg and (27.41) kg, respectively. These results agreed with the results of the study of the researcher [24], where they found an increase in the final weight whenever the percentage of protein in the diet increased when using different levels of protein, where the lambs were fed levels (110,140,170 and 200) g/kg, This study also agreed with the researchers' study [25] where the high protein treatments were superior in final body weight to the control treatment, These results also agreed with what was found by [26], where they indicated that the final weight and empty body weight increased when lambs were fed high-protein diets, while they did not agree with what was found by [27], where they did not show any differences. Significant when using diets with a protein level (14,16,18 and 20%), also did not agree with what [28] indicated, because there were no significant differences when feeding the study lambs on diets with protein content (11,16%).…”
Section: Final and Empty Body Weightsupporting
confidence: 90%